2019
DOI: 10.1126/science.aav4040
|View full text |Cite
|
Sign up to set email alerts
|

The genomic history of the Iberian Peninsula over the past 8000 years

Abstract: We assembled genome-wide data from 271 ancient Iberians, of whom 176 are from the largely unsampled period after 2000 BCE, thereby providing a high-resolution time transect of the Iberian Peninsula. We document high genetic substructure between northwestern and southeastern hunter-gatherers before the spread of farming. We reveal sporadic contacts between Iberia and North Africa by~2500 BCE and, by~2000 BCE, the replacement of 40% of Iberia's ancestry and nearly 100% of its Y-chromosomes by people with Steppe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
338
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 398 publications
(381 citation statements)
references
References 107 publications
23
338
1
7
Order By: Relevance
“…While we cannot exclude influx from genetically similar populations such as early Iberian Bell Beakers, the absence of Steppe ancestry suggests genetic isolation from many Bronze Age mainland populations - including later Iberian Bell Beakers, who would already have carried substantial Steppe ancestry (O lalde et al , 2018). As further support, the Y haplogroup R1b-M269, the most frequent present-day western European haplogroup and the haplogroup associated with expansions that brought Steppe ancestry into Britain (O lalde et al , 2018) and Iberia (O lalde et al , 2019) about 2,500-2,000 BCE, remains absent in our sample of ancient Sardinian individuals through the end of our sampling period (1,200-1,000 BCE).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…While we cannot exclude influx from genetically similar populations such as early Iberian Bell Beakers, the absence of Steppe ancestry suggests genetic isolation from many Bronze Age mainland populations - including later Iberian Bell Beakers, who would already have carried substantial Steppe ancestry (O lalde et al , 2018). As further support, the Y haplogroup R1b-M269, the most frequent present-day western European haplogroup and the haplogroup associated with expansions that brought Steppe ancestry into Britain (O lalde et al , 2018) and Iberia (O lalde et al , 2019) about 2,500-2,000 BCE, remains absent in our sample of ancient Sardinian individuals through the end of our sampling period (1,200-1,000 BCE).…”
Section: Discussionsupporting
confidence: 64%
“…A plausible explanation arises from the observation that both Basque and Sardinians have remained relatively isolated since the Neolithic transition (e.g. see O lalde et al , 2019, for novel aDNA evidence on the Basque). While both Basque and Sardinians have received some immigration, apparently from different sources, both populations also retained an exceptionally high fraction of EEF ancestry (e.g., Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Olalde et al 51 detected a previously unrecognized genomic turnover during a 400-year period in the Iberian Bronze Age. The scale of this replacement is large (about 40% of the total ancestry was replaced), but is also remarkably gender-biased: about 100% of all Y-chromosomes were replaced.…”
Section: Sex Biases In Migrationmentioning
confidence: 99%
“…We may never know the specific details of their travels, but traces of their movement can be evinced from unlikely patterns of ancestry or relatedness (Box 1). For example, Olalde et al 51 found that a 4,400-year-old individual found buried near Madrid had North African ancestry, suggesting he or his direct ancestors may have been recent migrants into the Iberian peninsula 51 . Moreover, the same study revealed that a woman from a V-VIth century CE Visigothic site in Girona (Northeast Spain) had clear affinities to Eastern Europeans, and could therefore have travelled from there or have relatives there, perhaps as a consequence of the recent Goth invasion into the Roman Empire.…”
Section: Individual Journeys and Mobilitymentioning
confidence: 99%
“…For the 14 individuals with additional libraries, new sequencing data were merged with data 166 from [3], and Y-chromosome calls from [3] were updated accordingly ( Table 1). 167 168 We determined genetic sex based on the ratio of Y chromosome to sum of X and Y chromosome 169 sequences [36] and relatedness coefficients using the method in [37] with nucleotide mismatch rate 170 of 0.127. For Principal Component Analysis (PCA), a random allele was sampled for each ancient Results 183 184 Archaeology and Bio-Anthropology 185 The 24 graves make Irlbach the largest Bell Beaker culture cemetery in South Germany discovered to 186 date.…”
mentioning
confidence: 99%